Prognostic and predictive value of fibroblast growth factor receptor alterations in high-grade non-muscle-invasive bladder cancer treated with and without bacillus Calmette-Guérin immunotherapy: bladder cancer - Mayr, Roman; Eckstein, Markus; Wirtz, Ralph M.; Santiago-Walker, Ademi; Baig, Mahadi; Sundaram, Ramesh; Carcione, Jenna Cody; Stoehr, Robert; Hartmann, Arndt; Bolenz, Christian; Burger, Maximilian; Otto, Wolfgang; et al. (European urology, 2022)
Background - Limited data are available on the prognostic and predictive value of fibroblast growth factor receptor alterations (FGFRa) relative to clinical outcomes in patients with non-muscle-invasive bladder cancer (NMIBC). - Objective - To determine whether FGFRa may be clinically useful in stratifying for treatment response in a real-world cohort of patients with pT1 NMIBC treated and untreated with bacillus Calmette-Guérin (BCG) instillation therapy. - Design, setting, and participants - A pooled dataset of matched clinical and genomic data (1992-2015) for pT1 NMIBC patients was assessed by the Bladder Cancer Research Initiative for Drug Targets in Germany consortium. - Outcome measurements and statistical analysis - Key efficacy outcomes were recurrence-free survival (RFS), progression-free survival (PFS), and disease-specific survival (DSS), which were estimated by Kaplan-Meier analysis, with hazard ratios calculated using a multivariate Cox proportional-hazard model. - Results and limitations - In this retrospective study of 263 patients with high-grade NMIBC, at a median follow-up of 63 mo, 32% showed recurrence and 15% progressed to muscle-invasive bladder cancer. FGFRa were found in 43% of patients, including 39% mutations and 5.7% fusions. FGFRa were associated with lower rates of concomitant carcinoma in situ. Among patients with or without FGFRa, there was no significant difference in PFS, RFS, and DSS in those who were BCG treated or BCG naive, or in the overall population. Limitations include the retrospective design from a single-center setting. - Conclusions - In patients with high-risk NMIBC, FGFRa were frequently observed. Patients with FGFRa who often exhibit recurrence/relapse after BCG treatment have a high unmet need. - Patient summary - Our retrospective study suggests that fibroblast growth factor receptor alterations (FGFRa) occur frequently in non-muscle-invasive bladder cancer (NMIBC). Outcomes were similar with or without FGFRa in patients with NMIBC, both overall and for standard bacillus Calmette-Guérin (BCG) treatment.
Online verfügbar: 26. März 2022, Artikelversion: 27. Mai 2022
Gesehen am 30.01.2024